Early acute kidney injury and transition to renal replacement therapy in critically ill patients with SARS-CoV-2 requiring veno-venous extracorporeal membrane oxygenation - Kevin Roedl; Silvia De Rosa; Marlene Fischer; Josephine Braunsteiner; Christian Schmidt-Lauber; Dominik Jarczak; Tobias B. Huber; Stefan Kluge; Dominic Wichmann (Annals of Intensive Care, 2023)
Abstract Background Critically ill patients with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) requiring veno-venous extracorporeal membrane oxygenation (vv-ECMO) are at risk for acute kidney injury (AKI). Currently, the incidence of AKI and progression to kidney replacement therapy (RRT) in critically ill patients with vv-ECMO for severe COVID-19 and implications on outcome are still unclear. Methods Retrospective analysis at the University Medical Center Hamburg-Eppendorf (Germany) between March 1st, 2020 and July 31st, 2021. Demographics, clinical parameters, AKI, type of organ support, length of ICU stay, mortality and severity scores were assessed. Results Ninety-one critically ill patients with SARS-CoV-2 requiring ECMO were included. The median age of the study population was 57 (IQR 49–64) years and 67% (n = 61) were male. The median SAPS II and SOFA Score on admission were 40 (34–46) and 12 (10–14) points, respectively. We observed that 45% (n = 41) developed early-AKI, 38% (n = 35) late-AKI and 16% (n = 15) no AKI during the ICU stay. Overall, 70% (n = 64) of patients required RRT during the ICU stay, 93% with early-AKI and 74% with late-AKI. Risk factors for early-AKI were younger age (OR 0.94, 95% CI 0.90–0.99, p = 0.02) and SAPS II (OR 1.12, 95% CI 1.06–1.19, p < 0.001). Patients with and without RRT were comparable regarding baseline characteristics. SAPS II (41 vs. 37 points, p < 0.05) and SOFA score (13 vs. 12 points, p < 0.05) on admission were significantly higher in patients receiving RRT. The median duration of ICU (36 vs. 28 days, p = 0.27) stay was longer in patients with RRT. An ICU mortality rate in patients with RRT in 69% (n = 44) and in patients without RRT of 56% (n = 27) was observed (p = 0.23). Conclusion Critically ill patients with severe SARS-CoV-2 related ARDS requiring vv-ECMO are at high risk of early acute kidney injury. Early-AKI is associated with age and severity of illness, and presents with high need for RRT. Mortality in patients with RRT was comparable to patients without RRT.